Family Planning Education to Advance SDGs with Insights on Fertility and Stunting Reduction - Aguk Budi Santoso; Harsuko Riniwati; Rosihan Asmara; Bunga Hidayati; Ahmad Khalid Salah (Journal of Nonformal Education, 2024)
Bojonegoro Regency is a 30% contributor to national oil, this certainly affects the regional budget with the highest ranking in Indonesia in 2022. but with this high regional income has not been able to reduce the poverty rate at 10%, this is due to several influencing factors. This research investigates the role of sustainable development policies, to find out how the participation of the Bojonegoro Regency community in handling Parity and stunting prevention, with research focusing on the fields of education, economy, health, social, culture, environment and population, in improving living standards in Bojonegoro Regency, Indonesia. Employing the Structural Equation Model (SEM) to analyze the interrelations among contraceptive use, parity, stunting, and sustainable development. Data collection in this study used documentation and questionnaires at the district and subdistrict levels. The findings highlight that while parity intervention through family planning education did not significantly influence sustainable development (Tvalue = 0.050), interventions aimed at stunting prevention through family planning education significantly contributed to sustainable development goals (Tvalues of 8.402 and 2.758, respectively). Additionally, the direct impact of family planning education on sustainable development was moderately significant (Tvalue = 1.740), suggesting the nuanced role of contraceptive methods in achieving broader development objectives. The study concludes that integrated family planning education and stunting prevention strategies are vital for sustainable development in Bojonegoro, contributing significantly to the discourse on public health and development policy. This research underscores the importance of tailored interventions in family planning education and health education as a means to foster sustainable development, offering valuable insights for policymakers and stakeholders in similar socio-economic contexts.